ON THE ESSENCE OF THE LEGAL PRESUMPTION - Virabyan, Gevorg (State and Law, 2022)
In the framework of this article, the author has discussed some methodological issues regarding the essence of the legal presumption. In particular, a range of these issues, methodological approaches to them that exist in the legal doctrine were presented. Certain situations have been considered in the form of examples, in the context of which it has been argued that the existing approaches in the legal doctrine do not allow to reveal the essence of the legal presumption. Then the author presented his theoretical-methodological vision for solving the isolated issues. In this context, he discussed the essence of the legal presumption, answered the question what the presumption is in legal terms, what does it allow to do within the framework of legal regulation, how does it relate to the forms (reasoning/judgment) of logical thinking.